Taxon- and Site-Specific Melatonin Catabolism - Rüdiger Hardeland (Molecules, 2017)
Melatonin is catabolized both enzymatically and nonenzymatically. Nonenzymatic processes mediated by free radicals, singlet oxygen, other reactive intermediates such as HOCl and peroxynitrite, or pseudoenzymatic mechanisms are not species- or tissue-specific, but vary considerably in their extent. Higher rates of nonenzymatic melatonin metabolism can be expected upon UV exposure, e.g., in plants and in the human skin. Additionally, melatonin is more strongly nonenzymatically degraded at sites of inflammation. Typical products are several hydroxylated derivatives of melatonin and N1-acetyl-N2-formyl-5-methoxykynuramine (AFMK). Most of these products are also formed by enzymatic catalysis. Considerable taxon- and site-specific differences are observed in the main enzymatic routes of catabolism. Formation of 6-hydroxymelatonin by cytochrome P450 subforms are prevailing in vertebrates, predominantly in the liver, but also in the brain. In pineal gland and non-mammalian retina, deacetylation to 5-methoxytryptamine (5-MT) plays a certain role. This pathway is quantitatively prevalent in dinoflagellates, in which 5-MT induces cyst formation and is further converted to 5-methoxyindole-3-acetic acid, an end product released to the water. In plants, the major route is catalyzed by melatonin 2-hydroxylase, whose product is tautomerized to 3-acetamidoethyl-3-hydroxy-5-methoxyindolin-2-one (AMIO), which exceeds the levels of melatonin. Formation and properties of various secondary products are discussed.